Inhalation of Atmospheric-Pressure Gas Plasma Attenuates Brain Infarction in Rats With Experimental Ischemic Stroke - Chen, Ye; Yang, Bingyan; Xu, Lixin; Shi, Zhongfang; Han, Ruoyu; Yuan, Fang; Ouyang, Jiting; Yan, Xu; Ostrikov, Kostya Ken (Frontiers in Neuroscience, 2022)
Previous studies suggest potential efficacy of neuroprotective effects of gaseous atmospheric pressure plasma (APP) treatment on neuronal cells. However, it remains unclear if neuroprotective properties of the gas plasmas benefit the ischemic stroke treatment, and how to use the plasmas in the in vivo ischemic stroke models. Rats were subjected to 90 min middle cerebral artery occlusion (MCAO) to establish the ischemic stroke model and then intermittently inhaled the plasma for 2 min at 60 min MCAO. The regional cerebral blood flow (CBF) was monitored. Animal behavior scoring, magnetic resonance imaging (MRI), 2,3,5-triphenyltetrazolium chloride (TTC) staining and hematoxylin and eosin (HE) staining were performed to evaluate the therapeutic efficacy of the gas plasma inhalation on MCAO rats. Intermittent gas plasma inhalation by rats with experimental ischemic stroke could improve the neurological function, increase regional CBF and decrease brain infarction. Further MRI tests showed that the gas plasma inhalation could limit the ischemic lesion progression, which was beneficial to improve the outcomes of the MCAO rats. Post-stroke treatment with intermittent gas plasma inhalation could reduce the ischemic lesion progression and decrease cerebral infarction volume, which might provide a new promising strategy for ischemic stroke treatment.